AB0080 Serum interleukin-34 levels increase in rheumatoid arthritis but are not associated with joint damage. (23rd January 2014) - Choi, B.Y.; Yoo, J.J.; Choi, Y.S.; Kang, E.H.; Song, Y.W.; Lee, Y.J.
Abstract : Background: Interleukin-34 (IL-34) plays a critical role in osteoclastogenesis via colony-stimulating factor 1 receptor and enhances monocyte viability and chemokines production [1, 2]. Recently, Chemel et al. reported that the expression of IL-34 is increased in the RA synovium [3]. Objectives: The aim of this study was to explore whether interleukin-34 (IL-34) can contribute to disease activity and joint damage in rheumatoid arthritis (RA). Methods: 70 RA patients, 36 spondyloarthropathy (SpA) patients and 59 gender- and age- matched healthy controls were included in the study. When the sera were obtained, a complete blood count (CBC), erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) were measured and clinical assessments, including Disease Activity Score 28 (DAS28), were performed. Joint damage was assessed using the simplified erosion and narrowing score (SENS). Synovial fluid (SF) samples were also collected from 18 RA patients and 19 osteoarthritis (OA) patients. IL-34 levels in serum and SF were determined by using ELISA. Immunohistochemistry was performed in synovial biopsies from RA patients. Results: Serum IL-34 levels in patients with RA or SpA were significantly higher than those in controls (p<0.0001, respectively). SF IL-34 levels were also significantly higher in RA patients than SF levels of OA patients (p<0.0001) and serum levels of RA patients (p<0.001). Subgroup analyses showed that serum IL-34 levels were significantly higher in early RA (disease duration ≤6 months, n=21) than in late RA (n=49, p<0.05). In all subjects, serum IL-34 concentrations were significantly correlated with the levels of ESR and CRP and blood leukocyte and monocyte counts. However, serum IL-34 levels in RA patients were not correlated with clinical disease activity indexes including DAS28 and were not associated with the SENS scores, presence of joint damage or osteoporosis, or use of corticosteroid or antirheumatic drugs. IL -34 expressions in RA synovial tissue were found in CD 68 positive cells. Conclusions: We confirmed that IL-34 levels in RA were elevated and found that early RA patients had higher serum IL-34 levels, suggesting that IL-34 may play a role in the early stage of RA synovitis. However, although IL-34 concentrations were correlated with several inflammatory markers, they were not associated with radiographic joint damage. We conclude that IL-34 is not a strong predictor of joint destruction in RA. References: Chen Z, Buki K, Vaaraniemi J, et al. The critical role of IL-34 in osteoclastogenesis. PLoS One 2011;6:e18689. Eda H, Zhang J, Keith RH, et al. Macrophage-colony stimulating factor and interleukin-34 induce chemokines in human whole blood. Cytokine 2010;52:215-20. Chemel M, Le Goff B, Brion R, et al. Interleukin 34 expression is associated with synovitis severity in rheumatoid arthritis patients. Ann Rheum Dis 2012;71:150-4. Disclosure of Interest: None Declared